Positive electrode active material, positive electrode plate thereof and lithium ion battery
By combining lithium cobalt oxide with O3 phase structure and lithium manganese oxide with O2 phase structure in the positive electrode active material of lithium cobalt oxide with O3 phase structure, the problem of low capacity of lithium cobalt oxide in the O3 phase structure is solved, and the energy density and optimal balance of performance of lithium ion batteries are achieved.
Patent Information
- Application Number
- CN202510159339.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The low capacity of lithium cobalt oxide in the O3 phase structure limits the increase in the energy density of lithium-ion batteries.
The combination of positive electrode active materials is adopted, including lithium cobalt oxide in the O3 phase structure and lithium manganese oxide in the O2 phase structure. The mass of lithium manganese oxide in the O2 phase structure accounts for 10% to 35% of the total mass, and the mass of lithium cobalt oxide in the O3 phase structure accounts for 65% to 90% of the total mass.
By combining lithium cobalt oxide in O3 phase structure and lithium manganese oxide in O2 phase structure, the advantages of the two are complementary, the gram capacity of the positive electrode active material is improved, the energy density of the lithium-ion battery is increased, and the balance between rate performance and cycle performance is optimized.
Smart Images

Figure CN119627089A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a positive electrode active material and a positive electrode sheet thereof, and a lithium ion battery. Background Art
[0002] With the rapid development of new energy technologies, lithium-ion batteries, especially lithium-ion batteries, have become key energy storage devices in the fields of portable electronic devices, electric vehicles, etc. Improving the energy density of batteries, extending their cycle life and improving their rate performance are one of the important goals of current lithium-ion battery research.
[0003] As a traditional positive electrode active material, lithium cobalt oxide with an O3 phase structure has good cycle stability and a high voltage platform, and therefore exhibits excellent electrochemical performance at high voltage. However, the low gram capacity of lithium cobalt oxide with an O3 phase structure limits the improvement of the energy density of lithium-ion batteries. Summary of the invention
[0004] In view of the problem that lithium cobalt oxide with an O3 phase structure in the above-mentioned prior art has low specific capacity and limits the energy density of lithium ion batteries, the present invention provides a positive electrode active material and a positive electrode sheet thereof, and a lithium ion battery.
[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows: The present invention provides a positive electrode active material, which includes lithium cobalt oxide with an O3 phase structure and lithium manganese oxide with an O2 phase structure; the mass of the lithium manganese oxide with an O2 phase structure accounts for 10% to 35% of the total mass of the positive electrode active material; the mass of the lithium cobalt oxide with an O3 phase structure accounts for 65% to 90% of the total mass of the positive electrode active material.
[0006] Furthermore, the mass of the lithium manganese oxide with the O2 phase structure accounts for 10% to 20% of the total mass of the positive electrode active material; the mass of the lithium cobalt oxide with the O3 phase structure accounts for 80% to 90% of the total mass of the positive electrode active material.
[0007] Furthermore, the median particle size Dv50 of the lithium manganese oxide with the O2 phase structure is 3.8-7.5 μm; the median particle size Dv50 of the lithium cobalt oxide with the O3 phase structure is 15.5-19.0 μm.
[0008] Furthermore, the median particle size Dv50 of the lithium manganese oxide with the O2 phase structure is 4.6-6.5 μm; the median particle size Dv50 of the lithium cobalt oxide with the O3 phase structure is 15.9-17.0 μm.
[0009] Furthermore, the ratio of the median particle size Dv50 of the lithium cobalt oxide with the O3 phase structure to the median particle size Dv50 of the lithium manganese oxide with the O2 phase structure is b, 2.5<b<4.2.
[0010] Furthermore, the positive electrode active material is a mixture of lithium cobalt oxide with an O3 phase structure and lithium manganese oxide with an O2 phase structure; the Dv10 of the mixture is 2.0~6.0μm, the Dv50 of the mixture is 13.0~18.0μm, the Dv90 of the mixture is 26.0~35.0μm, and the Dv99 of the mixture is 37.0~50.0μm.
[0011] Furthermore, the lithium manganese oxide with an O2 phase structure is a lithium manganese oxide with an O2 phase structure modified by bulk phase doping, and its chemical formula is aLi2MnO3·(1-a)Li x1 Na y1 Co 1-z1 N z1 O2, wherein 0.5<a<1, 0.8≤x1≤1.1, 0.01≤y1≤0.05, 0<z1<0.15; N is a doping element, and the N element includes one or more of Al, Ti, Mg, Ni, Mn, and Fe.
[0012] Furthermore, the lithium cobalt oxide with an O3 phase structure is a bulk phase doped and modified lithium cobalt oxide with an O3 phase structure, and its chemical formula is LiCo x2 M y2 O2, wherein 0.85≤x2<1, 0<y2≤0.15, x2+y2=1; M is a doping element, and the M element includes one or more of Al, Ti, Mg, Ni, Mn, La, Ce, Zr, Y, and W.
[0013] In a second aspect, the present invention provides a positive electrode plate, comprising a positive electrode collector and a positive electrode active material layer arranged on at least one side surface of the positive electrode collector, wherein the positive electrode active material layer comprises any one of the above-mentioned positive electrode active materials.
[0014] Furthermore, the compaction density ρ of the positive electrode sheet is 3.9-4.5 g / cm 3 .
[0015] In a third aspect, the present invention provides a lithium-ion battery, comprising the above-mentioned positive electrode plate, wherein the charging cut-off voltage of the lithium-ion battery is greater than or equal to 4.5V.
[0016] The beneficial effects of the present invention are: In the present invention, the positive electrode active material includes lithium cobalt oxide with an O3 phase structure and lithium manganese oxide with an O2 phase structure. On the one hand, O3 phase lithium cobalt oxide exhibits good structural stability under high voltage, which can effectively prevent the performance degradation of lithium ion batteries during long-term high voltage use, thereby significantly improving the cycle stability of lithium ion batteries and extending their service life; on the other hand, O2 phase structure lithium manganese oxide has a high gram capacity and excellent rate performance, which enables it to provide higher energy output during rapid charging and discharging, and can effectively improve the energy density of lithium ion batteries; in the present invention, by combining the two materials of O3 phase structure lithium cobalt oxide and O2 phase structure lithium manganese oxide, the advantages of the two are complemented; when the mass of the O2 phase structure lithium manganese oxide accounts for 10% to 35% of the total mass of the positive electrode active material; the mass of the O3 phase structure lithium cobalt oxide accounts for 65% to 90% of the total mass of the positive electrode active material, not only can the high voltage stability and long cycle life provided by the O3 phase structure lithium cobalt oxide be utilized, but also the high energy density and excellent rate performance of the O2 phase structure lithium manganese oxide can be brought into play, the gram capacity of the positive electrode active material is improved, the energy density of the lithium ion battery is increased, and the optimal balance among the energy density, rate performance and cycle performance of the lithium ion battery is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a SEM image of a positive electrode active material provided in one embodiment of the present invention. DETAILED DESCRIPTION
[0018] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0019] An embodiment of the present invention provides a positive electrode active material, which includes lithium cobalt oxide with an O3 phase structure and lithium manganese oxide with an O2 phase structure; the mass of the lithium manganese oxide with an O2 phase structure accounts for 10% to 35% of the total mass of the positive electrode active material; the mass of the lithium cobalt oxide with an O3 phase structure accounts for 65% to 90% of the total mass of the positive electrode active material.
[0020] In the present invention, the positive electrode active material includes lithium cobalt oxide with an O3 phase structure and lithium manganese oxide with an O2 phase structure. On the one hand, lithium cobalt oxide with an O3 phase structure exhibits good structural stability under high voltage, which can effectively prevent the performance degradation of lithium-ion batteries during long-term high-voltage use, thereby significantly improving the cycle stability of lithium-ion batteries and extending their service life; on the other hand, lithium manganese oxide with an O2 phase structure has a higher gram capacity and excellent rate performance, which enables it to provide higher energy output during rapid charging and discharging, and can effectively improve the energy density of lithium-ion batteries; in the present invention, by combining lithium cobalt oxide with an O3 phase structure and lithium manganese oxide with an O2 phase structure, the advantages of the two materials are complemented. When the proportion of lithium manganese oxide with an O2 phase structure in the total mass of the positive electrode active material is greater than 35%, the cycle performance of the lithium ion battery is poor; when the proportion of lithium manganese oxide with an O2 phase structure in the total mass of the positive electrode active material is less than 10wt%, the positive electrode active The gram capacity of the active material is small; when the proportion of lithium cobalt oxide with O3 phase structure in the total mass of the positive electrode active material is less than 65%, the long cycle performance of the positive electrode active material is poor; when the proportion of lithium cobalt oxide with O3 phase structure in the total mass of the positive electrode active material is higher than 90%, the gram capacity of the positive electrode active material is small; when the mass of lithium manganese oxide with O2 phase structure accounts for 10%~35% of the total mass of the positive electrode active material, and the mass of lithium cobalt oxide with O3 phase structure accounts for 65%~90% of the total mass of the positive electrode active material, it can not only utilize the high voltage stability and long cycle life provided by lithium cobalt oxide with O3 phase structure, but also give play to the high energy density and excellent rate performance of lithium manganese oxide with O2 phase structure, thereby improving the gram capacity of the positive electrode active material, increasing the energy density of lithium ion batteries, and achieving an optimized balance among the energy density, rate performance and cycle performance of lithium ion batteries.
[0021] Specifically, the mass of the lithium manganese oxide with the O2 phase structure may account for 10%, 12%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 35% or any value within the above range, or a range between any two values, which is not limited in the present application.
[0022] Specifically, the mass of the lithium cobalt oxide with the O3 phase structure may account for 65%, 68%, 70%, 73%, 75%, 78%, 80%, 83%, 85%, 87%, 90% or any value in the above range, or a range between any two values, which is not limited in the present application.
[0023] In some embodiments, the mass of the lithium manganese oxide with an O2 phase structure accounts for 10% to 20% of the total mass of the positive electrode active material; the mass of the lithium cobalt oxide with an O3 phase structure accounts for 80% to 90% of the total mass of the positive electrode active material.
[0024] Specifically, the mass of the lithium manganese oxide with the O2 phase structure may account for 10%, 12%, 14%, 16%, 18%, 20% of the total mass of the positive electrode active material, or any value within the above range, or a range between any two values, which is not limited in the present application.
[0025] Specifically, the mass of the lithium cobalt oxide with the O3 phase structure may account for 80%, 82%, 84%, 86%, 88%, 90% of the total mass of the positive electrode active material, or any value within the above range, or a range between any two values, which is not limited in the present application.
[0026] In the present invention, the mass ratio of lithium manganese oxide with an O2 phase structure to the total mass of the positive electrode active material is preferably 10% to 20%, and the mass ratio of lithium cobalt oxide with an O3 phase structure to the total mass of the positive electrode active material is preferably 80% to 90%. Within this preferred range, the mass proportion distribution of lithium manganese oxide with an O2 phase structure and lithium cobalt oxide with an O3 phase structure is more reasonable, so that the gram capacity, rate performance and cycle performance of the positive electrode active material can be maintained at a high level, avoiding a significant reduction in cycle performance due to an excessively high proportion of lithium manganese oxide with an O2 phase structure or a significant reduction in gram capacity and rate performance due to an excessively high proportion of lithium cobalt oxide with an O3 phase structure.
[0027] In some embodiments, the median particle size Dv50 of the lithium manganese oxide with the O2 phase structure is 3.8-7.5 μm; the median particle size Dv50 of the lithium cobalt oxide with the O3 phase structure is 15.5-19.0 μm.
[0028] Specifically, the median particle size Dv50 of the lithium manganese oxide with the O2 phase structure can be 3.8 μm, 4.0 μm, 5.0 μm, 6.0 μm, 7.0 μm, 7.5 μm or any value in the above range, or a range between any two values, which is not limited in the present application.
[0029] Specifically, the median particle size Dv50 of the lithium cobalt oxide with the O3 phase structure can be 15.5 μm, 16.0 μm, 17.0 μm, 18.0 μm, 19.0 μm or any value in the above range, or a range between any two values, which is not limited in the present application.
[0030] When the median particle size Dv50 of lithium manganese oxide with an O2 phase structure or lithium cobalt oxide with an O3 phase structure is too small, the particles of lithium manganese oxide with an O2 phase structure or lithium cobalt oxide with an O3 phase structure are smaller as a whole, the mechanical strength of the particles of lithium manganese oxide with an O2 phase structure or lithium cobalt oxide with an O3 phase structure is reduced, and it is difficult to resist the stress generated during the charging and discharging process of lithium ions, making the particles of lithium manganese oxide with an O2 phase structure or lithium cobalt oxide with an O3 phase structure easily damaged, thereby reducing the cycle performance of the lithium-ion battery.
[0031] When the median particle size Dv50 of lithium manganese oxide with an O2 phase structure or lithium cobalt oxide with an O3 phase structure is too large, the particles of lithium manganese oxide with an O2 phase structure or lithium cobalt oxide with an O3 phase structure are larger as a whole, and the migration path of lithium ions is increased, resulting in a decrease in the rate performance of the lithium-ion battery.
[0032] In some embodiments, the median particle size Dv50 of the lithium manganese oxide with the O2 phase structure is 4.6-6.5 μm; the median particle size Dv50 of the lithium cobalt oxide with the O3 phase structure is 15.9-17.0 μm.
[0033] In the present invention, the median particle size Dv50 of lithium manganese oxide with an O2 phase structure is preferably 4.6-6.5 μm, and the median particle size Dv50 of lithium cobalt oxide with an O3 phase structure is preferably 15.9-17.0 μm. Within this preferred range, the particle sizes of lithium manganese oxide with an O2 phase structure and lithium cobalt oxide with an O3 phase structure are more reasonably matched, which can keep the compaction density of the positive electrode sheet at a high level while avoiding the reduction of the rate performance of the lithium ion battery due to the excessively large particle size of lithium manganese oxide with an O3 phase structure and the reduction of the cycle performance of the lithium ion battery due to the excessively small particle size of lithium manganese oxide with an O2 phase structure and lithium cobalt oxide with an O3 phase structure, which is more conducive to maintaining the energy density, rate performance and cycle performance of the lithium ion battery in a balanced state.
[0034] Specifically, the median particle size Dv50 of lithium manganese oxide with an O2 phase structure can be selected as 4.6 μm, 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm or any value in the above range, or a range between any two values, and the present application does not limit this.
[0035] Specifically, the median particle size Dv50 of lithium cobalt oxide with an O3 phase structure can be selected as 15.9 μm, 16.0 μm, 16.5 μm, 17.0 μm or any value in the above range, or a range between any two values, which is not limited in the present application.
[0036] Figure 1 The SEM image of the positive electrode active material is shown in Figure 2. Figure 1 It can be seen that the particles of lithium cobalt oxide with O3 phase structure are larger overall, and the particles of lithium manganese oxide with O2 phase structure are smaller overall. Obviously, the median particle size of lithium cobalt oxide with O3 phase structure is larger, and the median particle size of lithium manganese oxide with O2 phase structure is smaller. The two are mixed in a certain proportion, for example, the mass ratio between lithium cobalt oxide with O3 phase structure and lithium manganese oxide with O2 phase structure = 9:1 or 8:2 or 7:3, which increases the compaction density of the positive electrode active material and further increases the energy density of the lithium-ion battery.
[0037] Specifically, the above Dv50 refers to the volume median particle size.
[0038] In some embodiments, the ratio of the median particle size Dv50 of the lithium cobalt oxide with the O3 phase structure to the median particle size Dv50 of the lithium manganese oxide with the O2 phase structure is b, 2.5<b<4.2.
[0039] In the present invention, when the ratio of the median particle size Dv50 of lithium cobalt oxide with an O3 phase structure to the median particle size Dv50 of lithium manganese oxide with an O2 phase structure is in the range of 2.5 to 4.2, the positive electrode active material has a more balanced compaction density and electrochemical performance.
[0040] In some embodiments, the positive electrode active material is a mixture of lithium cobalt oxide with an O3 phase structure and lithium manganese oxide with an O2 phase structure; the Dv10 of the mixture is 2.0~6.0 μm, the Dv50 of the mixture is 13.0~18.0 μm, the Dv90 of the mixture is 26.0~35.0 μm, and the Dv99 of the mixture is 37.0~50.0 μm.
[0041] In the present invention, the particle size of the mixture formed by lithium cobalt oxide with an O3 phase structure and lithium manganese oxide with an O2 phase structure, and the blending ratio of lithium cobalt oxide with an O3 phase structure and lithium manganese oxide with an O2 phase structure are reasonably adjusted, so that the voids of large-size lithium cobalt oxide particles with an O3 phase structure can be well filled, and the pressure resistance of lithium manganese oxide with an O2 phase structure can be improved, thereby improving the compaction density of the positive electrode sheet and further improving the energy density of the lithium ion battery.
[0042] In some embodiments, the lithium manganese oxide of the O2 phase structure is lithium manganese oxide of the O2 phase structure modified by bulk phase doping, and its chemical formula is aLi2MnO3·(1-a)Li x1 Na y1 Co 1-z1 N z1 O2, wherein 0.5<a<1, 0.8≤x1≤1.1, 0.01≤y1≤0.05, 0<z1<0.15; N is a doping element, and the N element includes one or more of Al, Ti, Mg, Ni, Mn, and Fe.
[0043] In the present invention, the doping of N elements (such as Al, Ti, Mg, Ni, Mn, Fe, etc.) can prevent the excessive migration or conversion of lithium ions in lithium manganate with an O2 phase structure during the charge and discharge process, effectively inhibit the loss of active lithium in lithium manganate with an O2 phase structure, thereby improving the cycle stability of lithium manganate with an O2 phase structure. Secondly, the introduction of N elements can improve the crystal structure of lithium manganate with an O2 phase structure, optimize the lithium ion transmission path inside it, expand the lithium ion transmission channel, and enable lithium ions to migrate more quickly during the charge and discharge process, thereby improving the rate performance of the material, and then improving the rapid charge and discharge capability of lithium-ion batteries.
[0044] Wherein: the value of a can be selected as 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 0.99 or any value in the above range, or the value range of a is the interval between any two values, which is not limited in this application.
[0045] The value of x1 can be selected as 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1 or any value in the above range, or the value range of x1 is the interval between any two values, which is not limited in this application.
[0046] The value of y1 can be selected as 0.01, 0.02, 0.03, 0.04, 0.05 or any value in the above range, or the value range of y1 is the interval between any two values, which is not limited in this application.
[0047] z1 is 0.01, 0.03, 0.05, 0.08, 0.1, 0.12, 0.14 or any value in the above range, or the value range of z1 is the interval between any two values, which is not limited in this application.
[0048] In some embodiments, the lithium cobalt oxide with an O3 phase structure is a bulk phase doped lithium cobalt oxide with an O3 phase structure, and its chemical formula is LiCo x2 M y2 O2, wherein 0.85≤x2<1, 0<y2≤0.15, x2+y2=1, M is a doping element, and the M element includes one or more of Al, Ti, Mg, Ni, Mn, La, Ce, Zr, Y, and W. When the doping amount of the M element is too high, the active Co element will be reduced, the gram capacity of the positive electrode active material will decrease, and at the same time, impurities other than lithium cobalt oxide with an O3 phase structure may be introduced. When 0.85≤x2<1, 0<y2≤0.15, it can ensure that the stability of the O3 phase lithium cobalt oxide structure is improved while reducing the loss of gram capacity, and no impurities are introduced.
[0049] Specifically, the value of x2 can be selected as 0.85, 0.87, 0.89, 0.91, 0.93, 0.95, 0.97, 0.99 or any value in the above range, or the value range of x2 is the interval between any two values, which is not limited in this application.
[0050] Specifically, the value of y2 can be selected as 0.01, 0.03, 0.05, 0.07, 0.09, 0.11, 0.13, 0.15 or any value in the above range, or the value range of y2 is the interval between any two values, which is not limited in this application.
[0051] In order to further improve the long cycle performance of lithium cobalt oxide with O3 phase structure under high voltage, in the present invention, lithium cobalt oxide with O3 phase structure is doped with M element. The doping of M element (such as Al, Ti, Mg, Ni, Mn, La, Ce, Zr, Y and W) reduces the Co³ in lithium cobalt oxide by stabilizing the transition metal oxidation state of the material. + / Co 4+ The reduction-oxidation reaction activity of the O3 phase structure is reduced, thereby reducing the release of excess oxygen and the phase transition caused by it. This makes the O3 phase structure of lithium cobalt oxide have a more stable bulk structure under high voltage. Since the doping of M elements can improve the lattice stability of the O3 phase structure of lithium cobalt oxide and alleviate the harmful phase transition under high voltage, this directly enhances the cycle stability of the O3 phase structure of lithium cobalt oxide.
[0052] In the present invention, the doping of element M will lead to a decrease in the gram capacity of lithium cobalt oxide with an O3 phase structure. Therefore, the doping amount y2 of element M is controlled within the range of 0<y2≤0.15 to balance the gram capacity, high voltage lattice stability and cycle performance of lithium cobalt oxide with an O3 phase structure.
[0053] On the other hand, an embodiment of the present invention provides a positive electrode plate, including a positive electrode collector and a positive electrode active material layer arranged on at least one side of the positive electrode collector, wherein the positive electrode active material layer includes the positive electrode active material described in any of the above embodiments.
[0054] In some embodiments, the compaction density ρ of the positive electrode sheet is 3.9-4.5 g / cm 3 Among them, ρ can be selected as 3.9g / cm 3 , 4.1g / cm 3 , 4.3g / cm 3 4.5g / cm 3 Or any value in the above range, or the value range of ρ is the interval between any two values, which is not limited in this application.
[0055] Specifically, the compaction density of the positive electrode plate is a double-sided compaction density.
[0056] In the present invention, when the mass of the lithium manganese oxide with the O2 phase structure accounts for 10% to 35% of the total mass of the positive electrode active material; the mass of the lithium cobalt oxide with the O3 phase structure accounts for 65% to 90% of the total mass of the positive electrode active material, the compaction density ρ of the prepared positive electrode sheet is 3.9 to 4.5 g / cm 3 Within this range, it is possible to utilize the high voltage stability and long cycle life provided by lithium cobalt oxide with an O3 phase structure, and the high energy density and excellent rate performance of lithium manganese oxide with an O2 phase structure, thereby increasing the gram capacity of the positive electrode active material, increasing the energy density of lithium-ion batteries, and achieving an optimized balance among the energy density, rate performance, and cycle performance of lithium-ion batteries.
[0057] In some embodiments, the positive electrode active material layer further includes a conductive agent and a binder.
[0058] In some embodiments, the mass ratio of the positive electrode active material, the conductive agent and the binder in the positive electrode active material layer is: (80-99): (0.3-10): (0.5-15); preferably, the ratio is: (90-98.5): (1-8): (1-8). In this ratio, the positive electrode active material accounts for a relatively high proportion, which is beneficial to increase the material loading of the lithium ion battery, thereby increasing the capacity of the lithium ion battery.
[0059] Specifically, the conductive agent includes but is not limited to one or more of Super-P, conductive nanotubes, nanofibers, graphene, lamellar graphite sheets, carbon black, acetylene black, Ketjen black, graphene microspheres, three-dimensional conductive metal organic frameworks, porous spherical carbon, porous silica, porous alumina and porous titanium dioxide.
[0060] Specifically, the binder includes but is not limited to one or more of carboxymethyl cellulose (CMC), polytetrafluoroethylene (PTFE) and modified polymers thereof, rubber, styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polyimide (PI), modified polyimide, polypropylene, modified polypropylene, polyacrylic acid (PAA), modified polyacrylic acid, polyvinyl alcohol, modified polyvinyl alcohol, polyvinyl butyral, modified polyvinyl butyral, polyacrylonitrile (PAN) and modified polyacrylonitrile.
[0061] On the other hand, an embodiment of the present invention provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode plate as described in any of the above embodiments, and the charging cut-off voltage of the lithium-ion battery is greater than or equal to 4.5V.
[0062] The present invention is further described below by way of examples.
[0063] This embodiment is used to illustrate the lithium ion battery disclosed in the present invention, and includes the following operating steps: Example 1
[0064] (1) Preparation of positive electrode active materials: The lithium cobalt oxide with an O3 phase structure and the lithium manganese oxide with an O2 phase structure are uniformly mixed to obtain a positive electrode active material.
[0065] (2) Preparation of positive electrode sheet: The positive electrode active material, binder polyvinylidene fluoride (PVDF), and conductive agent Super-P were uniformly mixed at a mass ratio of 94:3:3, and then a proper amount of N-methylpyrrolidone (NMP) solvent was added and stirred uniformly to obtain a positive electrode slurry.
[0066] The positive electrode slurry is evenly coated on the surface of a clean aluminum foil, and then placed in a vacuum oven at 90°C for 12 hours. The baked electrode sheet is then rolled and cut into round electrode sheets for use as positive electrode sheets.
[0067] (3) Preparation of negative electrode sheet: The negative electrode plate adopts a round lithium sheet with a diameter of 16mm and a thickness of 0.5mm.
[0068] (4) Preparation of electrolyte: The electrolyte uses lithium hexafluorophosphate (LiPF6) solution with a molar concentration of 1 mol / L. The solvent of the electrolyte is a mixed solvent composed of ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC), wherein the volume ratio of EC, DEC and EMC is 1:1:1.
[0069] (5) Preparation of diaphragm: The diaphragm adopts single-layer PP diaphragm.
[0070] (6) Assembly of lithium-ion batteries: The positive electrode sheet, lithium sheet, electrolyte and separator were assembled into a CR2032 button-type lithium-ion battery in a glove box filled with argon.
[0071] Embodiments 2 to 11 Examples 2 to 11 are used to compare and illustrate the positive electrode active material and the positive electrode sheet and lithium ion battery disclosed in the present invention, and include most of the operating steps in Example 1, except that the formulas and parameters in Table 1 and Table 3 are used.
[0072] Comparative Examples 1 to 6 Comparative Examples 1 to 6 are used to compare and illustrate the positive electrode active material and the positive electrode sheet and lithium ion battery disclosed in the present invention, and include most of the operating steps in Example 1, except that the formulas and parameters in Table 1 and Table 3 are used.
[0073] Comparative Examples 7 and 8 Comparative Examples 7 and 8 are used to compare and illustrate the positive electrode active material, positive electrode plate, and lithium-ion battery disclosed in the present invention, including most of the operating steps in Example 1, except that the positive electrode active material used in Comparative Example 7 is lithium cobalt oxide with an O2 phase structure, and the positive electrode active material used in Comparative Example 8 is a mixture of lithium cobalt oxide with an O2 phase structure and lithium cobalt oxide with an O3 phase structure. Please refer to the formulas and parameters in Tables 2 and 3 for details.
[0074] Table 1
[0075] Table 2
[0076] Note: ① In each example of Tables 1 and 2, A1 is 0.8Li2MnO3·0.2Li 0.92 Na 0.03 Co 0.95 Ti 0.05 O2, B1 is LiCo 0.95 Al 0.05 O2; A2 is 0.85Li2MnO3·0.15Li 0.94 Na 0.02 Co 0.96 Mn 0.04 O2, B2 for LiCo 0.97 La 0.03 O2; A3 is lithium cobalt oxide Li with O2 phase structure 0.97 Na 0.03 Co 0.97 Al 0.03 O2; ② The mass proportions in Table 1 are the ratio of lithium manganese oxide with an O2 phase structure to the total mass of the positive electrode active material, and the ratio of lithium cobalt oxide with an O3 phase structure to the total mass of the positive electrode active material; ③ b in Table 1 is the ratio of the median particle size Dv50 of lithium manganese oxide with O2 phase structure to the median particle size Dv50 of lithium cobalt oxide with O3 phase structure.
[0077] Table 3
[0078] Performance Testing: The positive electrode active materials and lithium ion batteries prepared in the above examples and comparative examples were subjected to the following performance tests: ① Physical and chemical tests were performed on the positive electrode active materials and the compaction density of the positive electrode sheets in the embodiments and comparative examples, including the particle size distribution of the positive electrode active materials and the compaction density of the positive electrode sheets. The test results are shown in Table 3.
[0079] ② Gram capacity test: The charge rate of the lithium-ion battery was set to 0.1C (1C=200mA / g), the charge cut-off voltage was 4.58V, the discharge rate was 0.1C, the discharge cut-off voltage was 3.0V, the discharge capacity was obtained, and then the discharge gram capacity was calculated. The test results are shown in Table 4.
[0080] ③Rate performance test: The charge rate was set to 0.1C, the charge cut-off voltage was 4.58V, the discharge cut-off voltage was 3.0V, and the discharge rates were 0.2C, 0.5C, 1.0C, 1.5C, 2.0C, and 3.0C. The discharge capacity at 0.1C was taken as the benchmark (100%), and the discharge capacity retention rate at different rates was calculated. The test results are shown in Table 4.
[0081] ④Cyclic performance test: The charge rate was set to 0.5C, the charge cut-off voltage was 4.58V, the discharge rate was set to 0.5C, the discharge cut-off voltage was 3.0V, and the cycle was 50 cycles. Taking the first cycle of the cycle as the benchmark (100%), the discharge capacity retention rate after 50 cycles was calculated. The test results are shown in Table 4.
[0082] Table 4
[0083] In the present invention, the compaction density of the positive electrode sheet is related to the amount and particle size of lithium manganese oxide with an O2 phase structure and lithium cobalt oxide with an O3 phase structure. As shown in Examples 1 to 9 in Table 1 and Table 3, when the amount of lithium manganese oxide with an O2 phase structure of small particles increases, more lithium manganese oxide with an O2 phase structure will be dispersed in the gaps of lithium cobalt oxide with an O3 phase structure of large particles, thereby increasing the density of the positive electrode active material, the gram capacity of the positive electrode active material and the compaction density of the positive electrode sheet. When the b value increases, that is, the greater the difference between the particle size of lithium manganese oxide with an O2 phase structure and the particle size of lithium cobalt oxide with an O3 phase structure, the easier it is for lithium manganese oxide with an O2 phase structure to enter the gaps of lithium cobalt oxide with an O3 phase structure of large particles, the more conducive it is to improve the density of the positive electrode active material, thereby increasing the compaction density of the positive electrode sheet to improve the energy density of the lithium ion battery.
[0084] In addition, the volume particle size of the positive electrode active material mixture is related to the particle size and dosage of lithium manganese oxide with an O2 phase structure and lithium cobalt oxide with an O3 phase structure. As shown in Examples 1 to 9 in Tables 1 and 3, when the dosage of lithium manganese oxide with an O2 phase structure increases and the dosage of lithium cobalt oxide with an O3 phase structure decreases, the volume particle size of the positive electrode active material mixture, such as Dv99, Dv90, Dv50, and Dv10, all decreases; conversely, Dv99, Dv90, Dv50, and Dv10 increase. When the particle size of lithium manganese oxide with an O2 phase structure or lithium cobalt oxide with an O3 phase structure decreases, the volume particle size of the positive electrode active material mixture, such as Dv99, Dv90, Dv50, and Dv10, all decreases; conversely, Dv99, Dv90, Dv50, and Dv10 increase.
[0085] It can be seen from the test results of Examples 1 to 3 in Table 4 that when the mass proportion of lithium manganese oxide with an O2 phase structure in the positive electrode active material increases, the gram capacity of the positive electrode active material increases, the rate performance of the lithium ion battery increases, and the cycle performance of the lithium ion battery decreases. This is because lithium manganese oxide with an O2 phase structure has a high gram capacity and excellent rate performance, which increases the gram capacity and rate performance of the lithium ion battery, can provide higher energy output and adapt to fast charging and discharging. However, the structural stability of lithium manganese oxide with an O2 phase structure is poor. When the amount of lithium manganese oxide with an O2 phase structure increases, the performance declines during long-term charging and discharging, resulting in a decrease in the cycle performance of the lithium ion battery.
[0086] It can be seen from the test results of Example 1 and Comparative Examples 1 to 4 in Table 4 that when the amount of lithium manganese oxide with an O2 phase structure is too small, the gram capacity of the positive electrode active material is too small, and the rate performance of the lithium ion battery is poor; when the amount of lithium manganese oxide with an O2 phase structure is too much, the cycle performance of the lithium ion battery is poor, and the balance between the gram capacity, rate performance and cycle performance is poor.
[0087] From the test results of Examples 1 to 3 and Comparative Examples 5 and 6 in Table 4, it can be seen that when the particle size of lithium manganese oxide with an O2 phase structure and lithium cobalt oxide with an O3 phase structure is too large, the difficulty of fully dispersing the positive electrode active material increases, resulting in the compaction density of the positive electrode sheet and thus reducing the energy density of the lithium ion battery. When the particle size of lithium manganese oxide with an O2 phase structure and lithium cobalt oxide with an O3 phase structure is too small, due to the reduction in the mechanical strength of lithium manganese oxide with an O2 phase structure and lithium cobalt oxide with an O3 phase structure, the ability to resist the stress generated during the lithium ion charge and discharge process is reduced, and the particles are easily damaged, which weakens the stability of the positive electrode active material and reduces the cycle performance of the lithium ion battery.
[0088] It can be seen from the test results of Examples 1, 4 and 5 in Table 4 that when the median particle size Dv50 of the lithium cobalt oxide with an O3 phase structure increases, that is, when the particle size of the lithium cobalt oxide with an O3 phase structure increases, the cycle performance of the lithium ion battery gradually improves. The reason is that when the particle size of the lithium cobalt oxide with an O3 phase structure increases, its own mechanical strength becomes larger, and its ability to resist the stress generated during the lithium ion charging and discharging process is enhanced. The particles are not easily damaged, making the positive electrode active material more stable, thereby improving the cycle performance of the lithium ion battery. At the same time, due to the increase in the particle size of the lithium cobalt oxide with an O3 phase structure, the migration path of lithium ions increases, resulting in a decrease in the rate performance of the lithium ion battery. Similarly, Examples 1, 6 to 9 also meet this rule.
[0089] The lithium manganese oxide with an O2 phase structure used in Example 10 is 0.85Li2MnO3·0.15Li 0.94 Na 0.02 Co 0.96 Mn 0.04O2, the lithium cobalt oxide with O3 phase structure used in Example 11 is LiCo 0.97 La 0.03 O2. It can be seen from the test results in Table 4 that, compared with Comparative Examples 1 to 6, the gram capacity of the positive electrode active material and the rate performance and cycle performance of the lithium ion battery in Examples 10 and 11 are more balanced.
[0090] In the present invention, it can be seen from the test results of Example 1 and Comparative Examples 7 to 8 in Table 4 that when the positive electrode active material is lithium cobalt oxide with an O2 phase structure, the cycle performance of the lithium ion battery is too low, and the balance of the overall electrochemical performance of the lithium ion battery is poor; when the positive electrode active material is a mixture of lithium cobalt oxide with an O2 phase structure and lithium cobalt oxide with an O3 phase structure, the gram capacity of the positive electrode active material and the balance of the rate performance and cycle performance of the lithium ion battery are better than those of lithium cobalt oxide with an O2 phase structure as the positive electrode active material; further, when the positive electrode active material is a mixture of lithium manganese oxide with an O2 phase structure and lithium cobalt oxide with an O3 phase structure, the gram capacity of the positive electrode active material and the balance of the rate performance and cycle performance of the lithium ion battery are optimal.
[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material includes lithium cobalt oxide with an O3 phase structure and lithium manganese oxide with an O2 phase structure; The mass of the lithium manganese oxide with the O2 phase structure accounts for 10% to 35% of the total mass of the positive electrode active material; The mass of the lithium cobalt oxide with the O3 phase structure accounts for 65% to 90% of the total mass of the positive electrode active material.
2. The positive electrode active material according to claim 1, characterized in that The mass of the lithium manganese oxide with the O2 phase structure accounts for 10% to 20% of the total mass of the positive electrode active material; The mass of the lithium cobalt oxide with the O3 phase structure accounts for 80% to 90% of the total mass of the positive electrode active material.
3. The positive electrode active material according to claim 1, characterized in that The median particle size Dv50 of the lithium manganese oxide with the O2 phase structure is 3.8-7.5 μm; the median particle size Dv50 of the lithium cobalt oxide with the O3 phase structure is 15.5-19.0 μm.
4. The positive electrode active material according to claim 3, characterized in that The median particle size Dv50 of the lithium manganese oxide with the O2 phase structure is 4.6-6.5 μm; the median particle size Dv50 of the lithium cobalt oxide with the O3 phase structure is 15.9-17.0 μm.
5. The positive electrode active material according to claim 3, characterized in that The ratio of the median particle size Dv50 of the lithium cobalt oxide with the O3 phase structure to the median particle size Dv50 of the lithium manganese oxide with the O2 phase structure is b, 2.5<b<4.
2.
6. The positive electrode active material according to claim 3, characterized in that The positive electrode active material is a mixture of lithium cobalt oxide with an O3 phase structure and lithium manganese oxide with an O2 phase structure; the Dv10 of the mixture is 2.0-6.0 μm, the Dv50 of the mixture is 13.0-18.0 μm, the Dv90 of the mixture is 26.0-35.0 μm, and the Dv99 of the mixture is 37.0-50.0 μm.
7. The positive electrode active material according to claim 1, characterized in that The lithium manganese oxide with O2 phase structure is lithium manganese oxide with O2 phase structure modified by bulk phase doping, and its chemical formula is aLi2MnO3·(1-a)Li x1 Na y1 Co 1-z1 N z1 O2, wherein 0.5<a<1, 0.8≤x1≤1.1, 0.01≤y1≤0.05, 0<z1<0.15; N is a doping element, and the N element includes one or more of Al, Ti, Mg, Ni, Mn, and Fe.
8. The positive electrode active material according to claim 1, characterized in that The O3 phase structured lithium cobalt oxide is bulk phase doped modified O3 phase structured lithium cobalt oxide, and its chemical formula is LiCo x2 M y2 O2, wherein 0.85≤x2<1, 0<y2≤0.15, x2+y2=1; M is a doping element, and the M element includes one or more of Al, Ti, Mg, Ni, Mn, La, Ce, Zr, Y, and W.
9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 8.
10. The positive electrode sheet according to claim 9, characterized in that: The compaction density ρ of the positive electrode sheet is 3.9-4.5 g / cm 3 .
11. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode plate according to claim 9 or 10, and the charging cut-off voltage of the lithium-ion battery is greater than or equal to 4.5V.
Citation Information
Patent Citations
Positive electrode material and positive plate and battery comprising positive electrode material
CN115036474A
Positive electrode active material, method for producing same, and non-aqueous electrolyte secondary battery
CN118715633A
O2-phase lithium-rich positive electrode material for lithium ion battery and preparation method of O2-phase lithium-rich positive electrode material
CN119108551A
Method ofr prpearing high-lithium ion content laminated lithium manganate anode material
CN1719639A